Angular JS – The Newest Technology in Creating Web Applications - BUCEA-MANEA-TONIS, Radu (Annals of Spiru Haret University. Economic Series, 2016)
This article is the result of searching and selecting new technologies that help programmer in developing web applications. It also represents a pleading for using it, showing its advantages and disadvantages. Alongside the article there are features regarding binding elements, modules, filters and directives. It is a synthesis and a guide of good practice for innovative programmers. All technical issues presented are supported by a case study.